Kematian dalam Puisi “Jauh” Karya Joko Pinurbo: Kajian Semotika Riffaterre - Afrianto, M. Afdal; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2024)
The aim of this research is to analyze the meaning of the poem